Chemical constituents of Anacolosa frutescens - Alimboyoguen, Agnes B. (Animo Repository, 2014)
Chemical investigation of the dichloromethane extract of the leaves of Anacolosa frutescens afforded 3-acetylaleuritolic acid (1), β-amyrin (2) and a mixture of monounsaturated and saturated fatty acids. The structures of 1 and 2 were identified by comparison of their !3C NMR data with those reported in the literature.